Desenvolvimento de uma ferramenta assistiva médica de contexto específico em Libras - PINTO, Heitor Santa Rosa Soares (2024)
This paper presents the development of the Specific Context Medical Assistive Tool in Brazilian Sign Language, which facilitates communication between deaf patients and healthcare professionals by translating Libras into written Portuguese. The tool allows patients in medical consultations to describe symptoms in the context of Non-Communicable Chronic Diseases (NCDs), which can improve diagnostic accuracy, promote greater autonomy, and humanize care. Although focused on NCDs, the tool can be expanded to other areas. Future improvements include suggestions or auto-completion of phrases and the conversion of the constructed text into synthetic speech.